The Effect of Compensation and Work Discipline on Employee Performance in PT. Mahanusa Graha Persada - Risza Putri Elburdah; Qorine Nur Syafi’ina (Kusuma Negara Business School, 2021)
The purpose of this study was to determine the effect of compensation and work discipline on employee performance at PT Mahanusa Graha Persada either partially or simultaneously. The method used is the associative method. The sampling technique used is a saturated sample using a sample of 60 respondents. Data analysis used validity test, reliability test, classical assumption test, regression analysis, correlation coefficient analysis, determination coefficient analysis and hypothesis testing. The result of this study is that compensation has a significant effect on employee performance with the regression equation Y = 24.376 + 0.426X1, the correlation coefficient value is 0.426, meaning that both variables have a moderate level of relationship with a coefficient of determination of 21.7% and hypothesis testing is obtained t count > t table or (4,010 > 2,001). Work discipline has a significant effect on employee performance with the regression equation Y = 0.674 + 0.953X2, the correlation coefficient value is 0.953, meaning that both variables have a strong relationship with a coefficient of determination of 73.5% and hypothesis testing is obtained t count > t table or (12,672 > 2,001 ). Compensation and Work Discipline simultaneously have a significant effect on employee performance with the regression equation Y = 0.398 + 0.221X1 + 0.940X2. The correlation coefficient values ​​obtained are 0.221 (X1) and 0.940 (X2), meaning that the compensation variable (X1) has a moderate level of relationship and work discipline (X2) has a strong relationship level to employee performance (Y). The hypothesis test is obtained that the value of Fcount > Ftable or (79.067 > 3.16) thus Ho is rejected and H3 is accepted. This means that there is a simultaneous significant effect between compensation and work discipline on employee performance at PT. Mahanusa Graha Persada.